Prosthetic Stage of Implant Treatment in Missing Incisor Cases - P. Šimůnek; R. Foltán; T. Dostálová (Czech Dental Chamber, 2007)
Replacement of missing anterior tooth by implant is often associated with difficulties, particularly in case of central incisor. The choice of surgical and prosthetic procedure may influence the final result but positive and negative factors have to be evaluated from the start. Several anatomical limitations may preclude the ideal outcome of prosthetic treatment.